Determination of Edible Film Permeability Coefficients to Water Vapor, Oxygen, and Carbon Dioxide Transmission - Lastriyanto, Anang; Argo, Bambang Dwi; S., Sumardi H.; Komar, Nur; Hawa, La Choviya; Hermanto, Mochamad Bagus (Fakultas Teknologi Pertanian Universitas Brawijaya, 2007)
Edible film is commonly used in the preservation of fresh and minimally processed fruits. The suitability to be used for such purpose mainly determined by its physical characteristics like transmission properties, particularly its permeability to water vapour, oxygen and carbon dioxide. The research was conducted to determine the transmission properties of the edible film made up of low metoxyl pectins (LMP) as a primary component combined with stearic acid at a level of 0.25% v/v. Particular study was made to determine the permeability of the film towards water vapour, oxygen and carbon dioxide at various ranges of temperatures (5 to 28oC) and relative humidities (0 to 80%) examined on the film with thicknesses of 20 – 50 µm. The results indicated that the permeability coefficients of the film varied with transmitted substances. The values were 12.89 – 19.45 g.mm/ (m2.day.kPa) for water vapour, 3.26 – 28 mL.mm/(m2.day.kPa) for oxygen and 149 – 129 mL.mm/(m2.day.kPa) for carbon dioxide.Key words: LMP-based edible film, permeability coefficients